Sodium-ion battery electrode material preparation method and sodium-ion battery
Through quantitative mixing and multi-stage preheating treatment technology, the compaction density of the positive electrode material of sodium ion battery is improved, and the problems of high cost and complexity in the existing technology are solved, achieving the effect of improving battery performance and reducing costs.
Patent Information
- Application Number
- CN202411388453.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2025-01-07
AI Technical Summary
The compaction density improvement method of existing sodium ion battery positive electrode materials increases the production cost and complexity, limiting battery performance improvement and cost reduction.
By quantitatively weighing the sodium source, vanadium source, phosphate and carbon source, mixing it, multi-stage preheating and high-temperature heat treatment are carried out after forming the gel, the structure of vanadium phosphate is optimized and its compaction density is improved.
The compaction density of the sodium vanadium phosphate cathode material is significantly improved, the energy density and cycle stability of the battery are enhanced, and the use and cost of electrolyte are reduced.
Smart Images

Figure CN119263247A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of battery electrode preparation, and in particular to a method for preparing a sodium ion battery electrode material and a sodium ion battery. Background Art
[0002] In sodium-ion batteries, the performance of the cathode material directly determines key parameters such as the battery's energy density, cycle stability, and power density. Sodium vanadium phosphate (NaVOPO4), as a potential cathode material for sodium-ion batteries, has attracted attention due to its high theoretical specific capacity and stable electrochemical performance. Sodium vanadium phosphate has an olivine structure, a high theoretical specific capacity, and can provide good electrochemical performance. With the increasing demand for high-energy-density batteries, improving the compaction density of sodium vanadium phosphate cathode materials has become the key to the development of sodium-ion battery technology. This not only helps to improve battery performance, but also reduces costs to promote the application of sodium-ion batteries in large-scale energy storage and electric vehicles. However, the methods currently used to increase the compaction density of sodium vanadium phosphate, such as carbon coating, metal doping, nanostructure design, and composite technology, will increase the cost and complexity of preparation, which is not conducive to reducing battery costs and manufacturing. Summary of the invention
[0003] In order to overcome the deficiencies of the above-mentioned prior art, the present application provides a method for preparing a sodium ion battery electrode material and a sodium ion battery, which specifically adopts the following technical solutions:
[0004] A method for preparing a sodium ion battery electrode material comprises the following steps:
[0005] Step 1: quantitatively weigh a sodium source, a vanadium source, a phosphate and a carbon source, mix and dissolve them in water, heat and stir at 40° C. until the water is completely evaporated to form a gel;
[0006] Step 2: performing a first preheating treatment on the dried gel to form powder A;
[0007] Step 3: quantitatively weighing a sodium source, a vanadium source, a phosphate and a carbon source, mixing them thoroughly and then performing a second preheating treatment to form a powder B;
[0008] Step 4: Powder A and powder B are mixed evenly according to a certain proportion, and subjected to high-temperature heat treatment to obtain sodium vanadium phosphate with a high compaction density.
[0009] Optionally, the sodium source is one of sodium hydroxide, sodium carbonate or sodium bicarbonate.
[0010] Optionally, the vanadium source is vanadium pentoxide or ammonium metavanadate.
[0011] Optionally, the phosphate is one of diammonium phosphate or diammonium hydrogen phosphate.
[0012] Optionally, the carbon source is one of citric acid, oxalic acid or ammonium citrate.
[0013] Optional: When drying the gel in step 2, the gel is baked in an oven, wherein the oven temperature is set to 90-120°C and the baking time is set to 3 hours; when performing the first preheating treatment, high-temperature heating is performed in an argon or nitrogen atmosphere, wherein the heating temperature is set to 300-500°C and the heating time is set to 2-3 hours.
[0014] Optionally: When the mixed sodium source, vanadium source, phosphate and carbon source are subjected to a second preheating treatment in step three, high-temperature heating is performed under an argon or nitrogen atmosphere, wherein the heating temperature is set to 300-500° C. and the heating time is set to 2-3 hours.
[0015] Optionally, the mixing ratio of powder A and powder B in step 4 is (9-6): (1-4).
[0016] Optionally, when the mixed powder A and powder B are subjected to high-temperature heat treatment in step 4, high-temperature heating is performed under an argon atmosphere, wherein the heating temperature is set to 700-900° C. and the heating time is set to 8-10 hours.
[0017] Furthermore, the present application also discloses a sodium ion battery, comprising an electrode, wherein the electrode is prepared using the above-mentioned method for preparing sodium ion battery electrode materials.
[0018] Beneficial Effects
[0019] The technical solution of this application has the following beneficial effects:
[0020] The sodium ion battery electrode material preparation method of the present application significantly improves the compaction density of the sodium vanadium phosphate positive electrode material by optimizing the preparation process thereof, effectively increases the content of active substances per unit volume or weight, and further improves the volume energy density and weight energy density of the electrode, thereby improving the performance of the sodium ion battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a flow chart of the method for preparing sodium ion battery electrode materials in an embodiment of the present application. DETAILED DESCRIPTION
[0022] The present application is further described below in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and cannot be used to limit the scope of protection of the present application. It should be noted that the following detailed descriptions are all exemplary and are intended to provide further explanation of the present application.
[0023] For the production process of secondary batteries such as lithium-ion batteries and sodium-ion batteries, it is of great significance to improve the compaction density of positive electrode materials. First, increasing the compaction density of positive electrode materials can load more active materials into a limited battery volume, thereby increasing the energy density of the battery. Secondly, high compaction density helps to reduce the porosity inside the battery and reduce the internal resistance of the battery, thereby improving the charge and discharge performance of the battery. Thirdly, the structure of the compacted positive electrode material is more stable, which helps to improve the cycle life and thermal stability of the battery. Finally, high compaction density reduces the penetration of the electrolyte and reduces the amount of electrolyte used, which helps to reduce costs and reduce the impact on the environment. Therefore, increasing the compaction density of positive electrode materials has many benefits for improving battery performance and greatly promotes the research and manufacturing of battery materials.
[0024] Combination Figure 1 As shown, the present application specifically discloses a method for preparing a sodium ion battery electrode material, which can be applied to manufacture an electrode for a sodium ion battery, wherein the method comprises the following steps:
[0025] Step 1: quantitatively weigh a sodium source, a vanadium source, a phosphate and a carbon source, mix and dissolve them in water, heat and stir at 40°C until the water is completely evaporated to form a gel; it should be noted that the sodium source described in the present application is one of sodium hydroxide, sodium carbonate or sodium bicarbonate; the vanadium source is one of vanadium pentoxide or ammonium metavanadate; the phosphate is one of ammonium dihydrogen phosphate or diammonium hydrogen phosphate; the carbon source is one of citric acid, oxalic acid or ammonium citrate.
[0026] Step 2: After drying the gel, perform a first preheating treatment to form powder A; when drying the gel in step 2, use an oven to bake the gel, wherein the oven temperature is set to 90-120°C and the baking time is set to 3 hours; when performing the first preheating treatment, high-temperature heating is performed in an argon or nitrogen atmosphere, wherein the heating temperature is set to 300-500°C and the heating time is set to 2-3 hours.
[0027] Step three: quantitatively weigh the sodium source, vanadium source, phosphate and carbon source, mix them thoroughly and then perform a second preheating treatment to form powder B; in this step three, when the mixed sodium source, vanadium source, phosphate and carbon source are subjected to a second preheating treatment, they are heated at high temperature in an argon or nitrogen atmosphere, wherein the heating temperature is set to 300-500°C and the heating time is set to 2-3 hours.
[0028] Step 4: Powder A and powder B are mixed evenly in proportion, and subjected to high-temperature heat treatment to obtain high-density sodium vanadium phosphate. The mixing ratio of powder A and powder B in step 4 is (9-6): (1-4). Further, when the mixed powder A and powder B are subjected to high-temperature heat treatment, they are heated at high temperature in an argon atmosphere, wherein the heating temperature is set to 700-900°C, and the heating time is set to 8-10 hours.
[0029] The effect of the preparation method of the sodium ion battery electrode material of the present application is verified by the following examples and comparative examples. It should be noted that the purity specifications of all reagents in the following experiments are analytically pure, and the blue battery tester uses LANDCT2001A); the scanning electron microscope uses QUANTA FEG 250. If the specific experimental steps or conditions are not specified in the following examples, the operations or conditions of the conventional experimental steps described in the literature in this field can be followed. The reagents or instruments used without indicating the manufacturer are all conventional reagent products that can be purchased commercially.
[0030] Embodiment 1:
[0031] This embodiment 1 discloses a method for preparing a sodium ion battery electrode material, which comprises the following steps:
[0032] (1) Weigh 0.01 mol of vanadium pentoxide, 0.023 mol of oxalic acid, 0.03 mol of sodium hydroxide and 0.03 mol of ammonium dihydrogen phosphate and dissolve them in deionized water, and stir at 40° C. until the water in the solution evaporates to form a gel;
[0033] (2) transferring the gel obtained in step (1) into an oven, drying at 120° C. for 3 h to form a dry gel, and grinding the dried gel to obtain a dry gel powder;
[0034] (3) pre-calcining the dry gel powder obtained in step (2) at 300° C. for 2 h under a nitrogen atmosphere to obtain powder A;
[0035] (4) 0.01 mol of vanadium pentoxide, 0.023 mol of oxalic acid, 0.03 mol of sodium hydroxide and 0.03 mol of ammonium dihydrogen phosphate were weighed and mixed evenly, and then pre-calcined at 300° C. for 2 h under a nitrogen atmosphere to obtain powder B;
[0036] (5) Powder A and powder B were weighed in a mass ratio of A:B=9:1, mixed thoroughly, and calcined at 800°C for 8 h in an argon atmosphere to obtain carbon-coated sodium vanadium phosphate.
[0037] Embodiment 2:
[0038] This embodiment 2 discloses a method for preparing a sodium ion battery electrode material, which comprises the following steps:
[0039] (1) Weigh 0.02 mol of ammonium metavanadate, 0.025 mol of citric acid, 0.0165 mol of sodium carbonate and 0.03 mol of diammonium hydrogen phosphate and dissolve them in deionized water, and stir at 40° C. until the water in the solution evaporates to form a gel;
[0040] (2) transferring the gel obtained in step (1) into an oven, drying at 100° C. for 3 h to form a dry gel, and grinding the dry gel to obtain a dry gel powder;
[0041] (3) pre-calcining the dry gel powder obtained in step (2) at 500° C. for 2 h under an argon atmosphere to obtain powder A;
[0042] (4) Weigh 0.02 mol of ammonium metavanadate, 0.025 mol of citric acid, 0.0165 mol of sodium carbonate and 0.03 mol of diammonium hydrogen phosphate, mix them evenly, and pre-calcine them at 500° C. for 2 h under an argon atmosphere to obtain powder B;
[0043] (5) Powder A and powder B were weighed in a mass ratio of A:B=8:2, mixed thoroughly, and calcined at 900°C for 9 h in an argon atmosphere to obtain carbon-coated sodium vanadium phosphate.
[0044] Embodiment 3:
[0045] This embodiment 3 discloses a method for preparing a sodium ion battery electrode material, which comprises the following steps:
[0046] (1) Weigh 0.02 mol of ammonium metavanadate, 0.025 mol of ammonium citrate, 0.0165 mol of sodium bicarbonate, and 0.03 mol of ammonium dihydrogen phosphate, dissolve them in deionized water, and stir at 40° C. until the water in the solution evaporates to form a gel;
[0047] (2) transferring the gel obtained in step (1) into an oven, drying at 90° C. for 3 h to form a dry gel, and grinding the dried gel to obtain a dry gel powder;
[0048] (3) pre-calcining the dry gel powder obtained in step (2) at 400° C. for 3 h under an argon atmosphere to obtain powder A;
[0049] (4) Weigh 0.02 mol of ammonium metavanadate, 0.025 mol of ammonium citrate, 0.0165 mol of sodium bicarbonate and 0.03 mol of ammonium dihydrogen phosphate, mix them evenly, and pre-calcine them at 400° C. for 3 h under an argon atmosphere to obtain powder B;
[0050] (5) Powder A and powder B were weighed in a mass ratio of A:B=6:4, mixed thoroughly, and calcined at 700°C for 10 h in an argon atmosphere to obtain carbon-coated sodium vanadium phosphate.
[0051] Comparative Example 1:
[0052] This comparative example 1 discloses a method for preparing a sodium ion battery electrode material, which comprises the following steps:
[0053] (1) Weigh 0.02 mol of ammonium metavanadate, 0.025 mol of citric acid, 0.0165 mol of sodium carbonate and 0.03 mol of diammonium hydrogen phosphate and dissolve them in deionized water, and stir at 40° C. until the water in the solution evaporates to form a gel;
[0054] (2) transferring the gel obtained in step (1) into an oven, drying at 100° C. for 3 h to form a dry gel, and grinding the dry gel to obtain a dry gel powder;
[0055] (3) The dry gel powder obtained in step (2) was pre-calcined at 500° C. for 2 h under an argon atmosphere, and then the temperature was further raised to 900° C. and calcined for 9 h to obtain carbon-coated sodium vanadium phosphate.
[0056] Comparative Example 2:
[0057] This comparative example 2 discloses a method for preparing a sodium ion battery electrode material, which comprises the following steps:
[0058] (1) Weigh 0.02 mol of ammonium metavanadate, 0.025 mol of citric acid, 0.0165 mol of sodium carbonate and 0.03 mol of diammonium hydrogen phosphate, mix them evenly, and pre-calcine them at 500° C. for 2 h in an argon atmosphere;
[0059] (2) The temperature is continued to be raised to 900° C. and calcined for 9 hours to obtain carbon-coated sodium vanadium phosphate.
[0060] By testing the D of the materials obtained in the examples and comparative examples V 10. D V 50. D V 100, compaction density, first cycle capacity at 0.1C, coulombic efficiency and rate performance to verify the effect. The above test data are shown in Table 1:
[0061] Table 1
[0062]
[0063] It can be seen from Table 1 that the particle size of powder A prepared by the sol-gel method is smaller than the particle size of powder B prepared by the direct calcination method. By comparing the embodiments and the comparative examples, it can be seen that the compaction density of the mixed powder of the electrode material prepared by the method of the present application is significantly higher than that of the unmixed powder material. This is because the powder compaction density of the material is strongly correlated with the particle size of the powder. The present application uses multi-level particle size matching to fill the gaps of large particles with small particles, which can significantly improve the powder compaction density of the material. Furthermore, in terms of electrochemical performance of the electrode prepared by the method of the present application, the discharge capacity, coulomb efficiency and rate performance of the embodiments of the present application are significantly higher than those of the comparative example. This is because by increasing the compaction density, the content of active substances per unit volume or weight can be effectively increased, thereby increasing the volume energy density and weight energy density of the electrode.
[0064] The above is only a preferred implementation of the present application. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the technical principles of the present application. These improvements and modifications should also be regarded as the scope of protection of the present application.
Claims
1. A method for preparing a sodium ion battery electrode material, characterized in that: The steps include: Step 1: quantitatively weigh a sodium source, a vanadium source, a phosphate and a carbon source, mix and dissolve them in water, and heat and stir at 40° C. until the water is completely evaporated to form a gel; Step 2: performing a first preheating treatment on the dried gel to form powder A; Step 3: quantitatively weighing a sodium source, a vanadium source, a phosphate and a carbon source, mixing them thoroughly and then performing a second preheating treatment to form a powder B; Step 4: Powder A and powder B are mixed evenly according to a certain proportion, and subjected to high-temperature heat treatment to obtain sodium vanadium phosphate with a high compaction density.
2. The method for preparing a sodium ion battery electrode material according to claim 1, characterized in that: The sodium source is one of sodium hydroxide, sodium carbonate or sodium bicarbonate.
3. The method for preparing a sodium ion battery electrode material according to claim 1, characterized in that: The vanadium source is vanadium pentoxide or ammonium metavanadate.
4. The method for preparing a sodium ion battery electrode material according to claim 1, characterized in that: The phosphate is one of diammonium phosphate or diammonium hydrogen phosphate.
5. The method for preparing a sodium ion battery electrode material according to claim 1, characterized in that: The carbon source is one of citric acid, oxalic acid or ammonium citrate.
6. The method for preparing a sodium ion battery electrode material according to claim 1, characterized in that: When the gel is dried in the step 2, the gel is baked in an oven, wherein the oven temperature is set to 90-120°C and the baking time is set to 3 hours; when the first preheating treatment is performed, high-temperature heating is performed in an argon or nitrogen atmosphere, wherein the heating temperature is set to 300-500°C and the heating time is set to 2-3 hours.
7. The method for preparing a sodium ion battery electrode material according to claim 1, characterized in that: In the step 3, the mixed sodium source, vanadium source, phosphate and carbon source are subjected to a second preheating treatment by heating at high temperature in an argon or nitrogen atmosphere, wherein the heating temperature is set at 300-500° C. and the heating time is set at 2-3 hours.
8. The method for preparing a sodium ion battery electrode material according to claim 1, characterized in that: In the step 4, the mixing ratio of powder A and powder B is (9-6): (1-4).
9. The method for preparing a sodium ion battery electrode material according to claim 8, characterized in that: In the step 4, when the mixed powder A and powder B are subjected to high-temperature heat treatment, they are heated at high temperature in an argon atmosphere, wherein the heating temperature is set to 700-900° C. and the heating time is set to 8-10 hours.
10. A sodium ion battery comprising an electrode, characterized in that: The electrode is prepared by the method for preparing a sodium ion battery electrode material according to any one of claims 1 to 9.